Percutaneous Radiofrequency Ablation (RFA) in renal cancer. How to manage challenging masses. A narrative review - Ziglioli, Francesco; De Filippo, Massimo; Cavalieri, Domenico Maria; Pagnini, Francesco; Campobasso, Davide; Guarino, Giulio; Maestroni, Umberto (Acta Biomedica Atenei Parmensis, 2022)
In the last decades, the refinements in the imaging techniques led to an increased number of detected renal tumors. If radical and partial nephrectomy remain the gold standard for the treatment of renal cancer, Radio-Frequency Ablation (RFA) has emerged as a therapeutic option for renal masses. Even if this technique is minimally-invasive, it requires a proper preoperative anatomic study and in some cases RFA treatment is technically challenging. To date, there is no standardization for studying challenging cases before treatment and to plan a safe and effective procedure when intervening organs are in the trajectory of the needle.In this study we searched the literature focusing on the challenging cases and strategy applied to manage the treatment safely and effectively.MATERIALS AND METHODS. MedLine and Embase via Ovid database were searched, using the following key words: Percutaneous RFA, radiofrequency, renal ablation, kidney ablation, renal thermoablation, kidney thermoablation, hydrodissection, heat sink. The difficulties found in the literature while performing the ablation procedure were grouped and a categorization of the strategies applied to perform a safe and effective procedure was proposed, in the aim to standardize the approach for treatment of challenging cases.Literature was analyzed according with selection criteria agreed by the Authors.RESULTS. The literature review showed four groups of lesions requiring an experienced approach. Group 1: Lesions close to the bowel. Group 2: Lesions close to the urinary tract. Group 3: Lesions close to intervening organs. Group 4: Lesions close to large vessels (heat-sink phenomenon).CONCLUSION. When planning a RFA treatment, a standardized approach to challenging masses is possible. This review make the treatment of these masses more systematic and safe.